2016
DOI: 10.1111/sltb.12266
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐Related Guilt Mediates the Relationship between Posttraumatic Stress Disorder and Suicidal Ideation in OEF/OIF/OND Veterans

Abstract: Posttraumatic stress disorder (PTSD) and trauma-related guilt are risk factors for suicidal ideation (SI) in veterans. Components of trauma-related guilt were examined as serial mediators of the relationship between PTSD and SI. In a sample of 53 OEF/OIF/OND combat veterans, PTSD had an indirect effect on SI through a serial mediation chain of guilt cognitions, distress, and global guilt, suggesting that trauma-related guilt via cognitions, distress, and global guilt is a pathway from PTSD to SI. Attention sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Results from Bryan et al (2013) suggested that guilt and shame together mediated the relationship between PTSD and SI, and further research showed that guilt partially mediated the relationship between PTSD and SI (Bryan et al, 2015). A recent study of Iraq and Afghanistan veterans also showed that trauma-related guilt mediated the relationship between PTSD symptoms and SI (Tripp & McDevitt-Murphy, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from Bryan et al (2013) suggested that guilt and shame together mediated the relationship between PTSD and SI, and further research showed that guilt partially mediated the relationship between PTSD and SI (Bryan et al, 2015). A recent study of Iraq and Afghanistan veterans also showed that trauma-related guilt mediated the relationship between PTSD symptoms and SI (Tripp & McDevitt-Murphy, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…They found that guilt cognitions and distress had direct effects on PTSD and depressive symptoms, whereas global guilt did not. Tripp and McDevitt-Murphy (2016) tested the TRGI subscales as serial mediators of the relationship between PTSD and SI (refer to Figure 1A) and reported indirect effects of PTSD on SI via pathways through 1) guilt cognitions and global guilt, 2) distress and global guilt, and 3) the full model with all three subscales. These findings provided support for the existing model (i.e., Kubany & Watson, 2003) and evidence that trauma-related guilt may partially explain the relationship between PTSD symptoms and SI.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, although the relationship between two or three items guilt, intrusive rumination, deliberate rumination, PTSD, and suicide risk have been examined in previous studies, the role of intrusive rumination, deliberate rumination and PTSD in the impact of guilt on suicide risk has not been explored. Previous studies investigating guilt as an important factor in suicide risk have mostly been conducted in individuals who fulfill military service or veterans (Bryan et al, 2013;Hendin & Haas, 1991;Tripp & McDevitt-Murphy, 2017). Research focusing on the effect of guilt on suicide risk in adolescent survivors of earthquakes is scarce.…”
Section: The Present Studymentioning
confidence: 99%
“…We certainly know that peri-traumatic and post-traumatic guilt cognitions can make PTSD symptoms worse (Browne et al, 2015) and that trauma-related guilt can be so distressing that it mediates the link between PTSD and suicidality (Cunningham et al, 2017;Tripp and McDevitt-Murphy, 2017). Indeed, guilt has been associated with PTSD in a range of populations (Pugh et al, 2015), including refugees (Stotz et al, 2015), veterans (Dedert et al, 2019;Henning and Frueh, 1997;Litz et al, 2009), and survivors of domestic violence (Beck et al, 2011;Street et al, 2005).…”
Section: Why Intervene To Help With Guilt?mentioning
confidence: 99%